Environmental and economic evaluation of land use environmental included as structural elements in system ecological network Ukraine - Lobunko, Y. (Землеустрій, кадастр і моніторинг земель, 2017)
Done approaches to study ecological and economic assessment of environmental efficiency of land use, which included as a structural element in the system of ecological network of Ukraine. In particular, the proposed systematic approach to evaluating three different areas of conservation land.